Peningkatan Hasil Belajar, Aktivitas, dan Efikasi Diri Melalui Pembelajaran Model Carousel Feedback dan Showdown Pada Mata Pelajaran Kewirausahaan - Jefry Aulia Martha (Universitas Kanjuruhan Malang, 2015)
The aim of this study is to improve student’s learning outcome, activity, and self efficacy in Enterpreunership course apply cooperative learning colaboration of Carousel Feedback and Showdown model. This study contained of two cycles in which each cycle contained of three times meeting. Each cycle contained of planning, acting & observating, reflecting, and revise plan. The data collections used in this study were using test, observation sheet, questionnaire, field note, and documentation. The subject was 32 students in the 10th grade students of Multimedia at SMKN 1 Bondowoso. The result of this study showed that after implementing Carousel Feedback and Showdown model student’s learning outcome, activity, and self efficacy increased from cycle I to cycle II. Student’s learning outcome has increased from 73,44% at the first cycle to 86,84% at the second cycle. Student’s activity increased from 60% at the first cycle to 79% at the second cycle. Application of Carousel Feedback and Showdown can also increase student’s efficacy. Twenty five students have very high self-efficacy at the second cycle increase from 15 students at first cycle.